Reconstructing Productive, Connective, and Assimilative Numeracy Literacy Skills Using Flip Bookmaker Electronic Media - Suharna, Hery; Sulami; In Hi; Lamanisa (IJORER : International Journal of Recent Educational Research, 2025)
Objective: The purpose of this study is to see how the reconstruction of students' numeracy literacy skills through electronic media flip book maker. This is because literacy research is quantitative. Literacy is a very interesting topic of discussion today in the world of education. The difficulty of numeracy literacy in everyday life on campus is a challenge in itself. Method: Quantitative research type. Research subjects with categorization of numeracy literacy skills, namely very high, high and moderate based on the acquisition of pre-test and post-test data to classify based on ability, then based on the classification, how numeracy literacy is reconstructed. The analysis technique used is quantitative to classify literacy and qualitative to describe the reconstruction of numeracy literacy. The results of the study found (1) productive reconstruction occurred in very high category numeracy literacy skills, namely starting with improving numeracy literacy skills when disequilibration occurs and then carrying out productive knowledge reconstruction, (2) connective reconstruction occurred in high literacy skills, namely starting with improving numeracy literacy skills when disequilibration occurs in solving problems and then carrying out connective knowledge reconstruction and (3) assimilative reconstruction, namely with reconstruction with moderate category numeracy literacy skills, namely starting with improving numeracy literacy skills when disequilibration occurs in solving problems and then carrying out assimilative knowledge reconstruction. The novelty in this study reveals productive, connective and assimilation reconstruction in students' numeracy literacy skills. Productive, connective and assimilation reconstruction are initial data used in learning to map students' learning readiness, especially in mathematics learning.